CCT196969 inhibits TNBC by targeting the HDAC5/RXRA/ASNS axis to down-regulate asparagine synthesis - Qiong Yuan; Qi Wang; Jun Li; Liyang Yin; Shu Liu; Xuyu Zu; Yingying Shen (Journal of Experimental & Clinical Cancer Research)
Abstract Background Triple-negative breast cancer (TNBC) seriously threatens the health of patients, and new therapeutic targets and drugs need to be explored. Studies have shown that CCT196969 can inhibit melanoma and colorectal cancer. However, the role of CCT196969 in TNBC is unclear. Methods CCT196969 inhibited TNBC via in vitro and in vivo experiments. Transcriptomic analysis, metabolomics analysis, proteomic analysis, and other experiments were used to determine that CCT196969 inhibited asparagine synthetase (ASNS) expression and downstream mTOR signaling pathway, and that Retinoid X Receptor Alpha (RXRA) was the upstream transcription factor that regulated ASNS. The binding sites of RXRA and ASNS promoter were determined by luciferase and Chromatin Immunoprecipitation (CHIP) assay. Histone Deacetylase 5 (HDAC5) was confirmed as the key target of CCT196969 by target capture assay, Cell thermal shift assay (CETSA), Surface plasmon resonance (SPR) and other experiments. qPCR, CHX tracer, MG132, immunofluorescence (IF) and Co-Immunoprecipitation (CO-IP) assay were used to detect the regulation of HDAC5 on RXRA transcription and post-translation level, and the key domains of interaction and binding between HDAC5 and RXRA. The binding sites of HDAC5 and RXRA were predicted by PyMOL software. The effect of HDAC5 on the acetylation and ubiquitination levels of RXRA was examined by CO-IP experiment. The deacetylation site of HDAC5 to RXRA was investigated by IP experiments and mass spectrometry. Results This study reveals that CCT196969 can inhibit TNBC by down-regulating the expression of ASNS, inhibiting asparagine synthesis and downstream mTORC pathway. Mechanistically, CCT196969 targeted and inhibited HDAC5, reducing the interaction of its 1-291 region with RXRA’s 1–98 region, and further resulting in an increase in RXRA acetylation (K410 and K412) and a decrease in ubiquitination levels. Together, these effects up-regulated the transcriptional and post-translational levels of RXRA. Finally, RXRA inhibited the expression of ASNS at the transcriptional level by binding to the − 1114/-1104 region on the ASNS promoter as a transcription suppressor. Conclusions This study reveals a previously unrecognized anti-TNBC mechanism of CCT196969 through the HDAC5/RXRA/ASNS axis. This provides potential candidate targets for the treatment of TNBC and a theoretical basis for the clinical treatment of TNBC patients with CCT196969.